A new species of Dendroseius Karg from Iran (Acari: Rhodacaridae), with a key to the known species - Faraji, Farid; Sakenin-Chelav, Hamid; Karg, Wolfgang (Zootaxa, 2006)
Dendroseius amoliensis n. sp. collected from soil in northern Iran is described and illustrated. A key is provided for the known species of Dendroseius.